2022
DOI: 10.1089/cmb.2022.0002
|View full text |Cite
|
Sign up to set email alerts
|

Computational Analysis of High-Dimensional DNA Methylation Data for Cancer Prognosis

Abstract: Developing cancer prognostic models using multiomics data is a major goal of precision oncology. DNA methylation provides promising prognostic biomarkers, which have been used to predict survival and treatment response in solid tumor or plasma samples. This review article presents an overview of recently published computational analyses on DNA methylation for cancer prognosis. To address the challenges of survival analysis with high-dimensional methylation data, various feature selection methods have been appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 83 publications
0
1
0
Order By: Relevance
“…They absorb the beneficial electrons in our body and create disease. It is also the cause of various chronic diseases [19][20]. Antioxidants have the power to reduce its severity.…”
Section: Introductionmentioning
confidence: 99%
“…They absorb the beneficial electrons in our body and create disease. It is also the cause of various chronic diseases [19][20]. Antioxidants have the power to reduce its severity.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, liquid biopsy, as a noninvasive sampling method, can be applied continuously at multiple time points to assist in monitoring disease progression (20).Epigenetics encompasses heritable changes that do not alter the DNA sequence but significantly impact gene function. For instance, alterations in methylation patterns can enhance genomic instability, hindering the expression of tumour-suppressor genes (21)(22)(23). Recent research has demonstrated a clear association between changes in DNA methylation patterns and the development of breast cancer (24)(25)(26).…”
Section: Introductionmentioning
confidence: 99%